Key Determinants Of Online Repurchase Intentions In Malaysia - Lee, Chai Har (2010)
The objective of this research is to determine the factors that influence consumers\' intention to repurchase products and services online in Malaysia so that firms can provide more functional services based on customers\' requirements.This research provide useful information for online businesses in developing key responses to consumers\' needs and in building critical capabilities to create and maintain competitive positions in the marketplace.